A postfoundationalist research paradigm of practical theology - Pak, Sŏng-gyu (HTS teologiese studies, 2010)
Practical theology describes a context, interprets what has been discovered, brings in Christian norms, and constructs models of Christian practice. It is a process that involves epistemology and hermeneutics. For practical theology to be transformative, a postfoundational theological framework that allows interdisciplinary work and interpretation of experience in a given context is essential. Research in postfoundational practical theology can be conducted using narratives and social constructionism to obtain meaning from events or situations and to construct preferred realities.This article examines and argues for postfoundationalism – transversal reason, interdisciplinarity and interpreted experience – as a viable theological option against rigid foundationalism and relativistic nonfoundationalism. Also discussed are the process and the interdisciplinary nature of practical theology. It is suggested that narrative research and social constructionism should be part of the research paradigm of postfoundational practical theology.